Penerapan model pembelajaran argument driven inquiry (ADI) untuk meningkatkan kemampuan pemecahan masalah siswa kelas X SMA N 1 sinunukan pada materi usaha dan energi Tahun ajaran 2023/2024 - Meri Susanti; Sri Utami Kholilla Mora Siregar; Evitamala Siregar (JURNAL PENDIDIKAN ILMU PENGETAHUAN ALAM, 2024)
This study aims to obtain information about the Application of the Argument Driven Inquiry (ADI) Learning Model to Improve the Problem Solving Ability of Students of Class X Energy Business at SMA Negeri 1 Sinunukan. This research was carried out systematically, class X SMA Negeri 1 Sinunukan in the academic year 2023/2024, totaling 30 people. The type of research is Classroom Action Research following Kurt Lewin's model consisting of four steps, namely planning, action, observation, and reflection. Classroom Action Research with the cycle method. Qualitative research instruments are data reduction, data exposure, and data inference. The results showed that the students' understanding of physics learning on Energy Business increased by applying the Argument Driven Inquiry (ADI) learning model to improve the problemsolving ability of eighth grade students of SMA Negeri 1 J Sinunukan.